Complete Genome Sequence of the Thermoacidophilic Crenarchaeon Thermoproteus uzoniensis 768-20 - Mardanov, Andrey V. (American Society for Microbiology, 2011)
Thermoproteus uzoniensis 768-20 is a thermoacidophilic anaerobic crenarchaeon isolated from a solfataric field in Kamchatka, Russia. The complete genome sequence reveals genes for protein and carbohydrate-active enzymes, beta-oxidation of fatty acids, the Embden-Meyerhof and Entner-Doudoroff pathways for glucose metabolism, the tricarboxylic acid cycle, the dicarboxylate/4-hydroxybutyrate cycle, hydrogenase, and sulfur reductase.